Conceptualization of Communication Ethics Framework for Inter-religious Harmony: Study of Inter-Religious Harmony in the City of Kediri - Handayani, Diah (Proceedings of International Conference on Da'wa and Communication, 2023)
This research aims to show Islamic views through the Qur'an and Hadith regarding inter-religious harmony and then create a framework for the formation of communication ethics which can possibly be formed through reformulation of contextual interpretive meaning through Islamic views, historical descriptions and assessments regarding the ethics of inter-religious communication according to the textual Islamic view as a formula framework for an ethical approach to inter-religious communication, which not only can be seen for its validity philosophically, logically, and can be tested analytically, but can also be used as a practical reference in universal inter-religious communication practices considering the current conditions of inter-religious harmony. Paul Receur's Hermeneutic Phenomenology Approach is a form of approach that will be used to examine several frameworks of Al-Qur'an and Hadith texts relating to inter-religious harmony in this research. Research results show that the ethical approach in interreligious communication according to the textual Islamic perspective, is an approach or method by which people of different religions should communicate with each other in all matters, anywhere and in any relationship, optimally making ethicality a perspective and basis for consideration. Islam textually considers it important and has regulated broadly and in detail the approach by which people of different religions should communicate with each other in all matters, wherever and in any relationship, optimally making ethicality a point of view and basic considerations.